Bioecology of rice leaffolder, Cnaphalocrocis medinalis guenee (Lepidoptera: pyralidae) - Roseli, Marina (2019)
Rice leaffolder, Cnaphalocrocis medinalis Guenee is amongst the most destructive pests for rice causing significant damage of rice yield in many Asian countries including Malaysia. However, the information on biology and ecology on this pest in Malaysia is still lacking. Therefore, this study was conducted to i) determine the major lepidopteran rice pest and its associated parasitoids, ii) investigate population fluctuation of C. medinalis, iii) determine the life cycle of C. medinalis, and iv) construct life table and demographic parameters of C. medinalis. The distribution and abundance of lepidopteran rice pests and associated parasitoids were studied at four rice stages (30, 45, 60 and 75 days after sowing, DAS) in four locations namely Beseri (Perlis), Parit Buntar (Perak), Semanggol (Perak) and Tanjung Karang (Selangor). Population fluctuation of C. medinalis was studied in weekly interval during two consecutive seasons (main and off season) by picking the larvae from 10 hills which randomly selected in each three plots. Life cycle of C. medinalis was studied for determination of larval instar as well as the life table of C. medinalis. Results showed that C. medinalis was the most dominant species (88.00 ± 8.92 larvae) in all sampling locations. Its associated parasitoids were identified as Apanteles cypris, Apanteles sp., Bracon sp., Macrocentrus philippinensis and Argyrophylax cinerella. There was no significant difference in abundance of C. medinalis between main and off season. The population trend was similar in both seasons as the population was low at the beginning of season (vegetative phase) and gradually increase until the peak during reproductive phase. This is due to the morphology of rice plant during reproductive phase offers great suitability for larvae feeding. All three abiotic factors namely relative humidity, temperature and rainfall have contributed to the changes in population of C. medinalis with relative humidity contributed more than others. The factors greatly influence the insect population directly by limiting or expanding their distribution, growth, reproduction, diapause and dispersal. Cnaphalocrocis medinalis undergoes five larval instars with developmental period for egg, larva, prepupa and pupa ranged from 3-5, 17-26, 1-2 and 6-12 days, respectively. Age-specific survival (lx) indicated that 32.26% of C. medinalis eggs has successfully reached adult stage with average sex ratio of 0.96:1.00 (Female: Male). The highest mortality was recorded in first instar larvae (22.58%) with K-value of 0.125 and can be concluded as the key factor in regulating C. medinalis population. The pattern of survivorship curve falls into type III. Age-specific fecundity (mx) shows the earliest egg laying was on day 30 and the last female died on day 43. The female laid on average 104.33 ± 5.43 eggs. The intrinsic rate of natural increase (rm) was 0.08, net reproduction rate (Ro) of 14.48 and doubling time of 8.19 days. It shows that the population has built up in short time period. In conclusion, the rice leaffolder, Cnaphalocrocis medinalis was the major lepidopteran rice pests in Malaysian rice fields. The knowledge gained on the population fluctuation, natural enemies, life cycle and life table will facilitate farmers into better management on this lepidopteran rice pests.